Oratorio for Prague - Němec, Jan (Czechoslovakia, 1968)
Filmmaker Jan Nemec and his crew risked their lives to create this historic documentary account of the 1968 Soviet invasion of Czechoslovakia. The award-winning work is the only filmed record of the invasion. Oratorio for Prague begins as a study of the liberalization of Czechoslovakia and then continues when the Russian forces moved in. The gripping footage was broadcast by television, providing the first report of the event. In addition to the news footage, the film features never-before-viewed scenes taken prior to the invasion that crushed Prague's anti-Communist movement.